PELAKSANAAN PEMBELAJARAN SENI BUDAYA BERDASARKAN K13 DI SMP NEGERI 25 PADANG - Sari, Pinti Puspita; Yuliasma, Yuliasma (SENDRATASIK UNP, 2019)
Abstract This research aims to see how the process of implementing dance art learning K13, obstacles in the implementation of dance art K13 and the form of dance art assessment K13 in SMPN 25 Padang. This type of qualitative research is descriptive research with a qualitative approach. The instrument in this study is self-researcher and assisted with supporting instruments such as stationery and cameras. Data collection techniques are conducted by studying the library of observation, interviews and documentation. Data types use primary data and secondary data. The steps for analyzing data are data collection, classifying data, describing data and making conclusions. The results showed that the learning process of 2013 curriculum  in the Study of Cultural Arts (dance) in SMP N 25 Padang is not fully carried out according to the dimensions and direction of the 2013curriculum. Because teaching teachers always use the conventional method, while the teacher has gained training and curriculum knowledge 2013 about the implementation of learning. The 2013 curriculum rules only live rules and that teachers are implemented as per the will of the teacher, so even though K13 is already set up by the government but the teacher has not overall applied the K13 should. Keywords: implementation, cultural arts learning, 2013 curriculum